A study on the lipid peroxidation status and the antioxidant system in rats at experimental diabetic retinopathy - Semenko, Volodymyr Volodymyrovych; Serdyuk, Valeriy Mykolayovych; Savytskyi, Ivan Volodymyrovych (Journal of Education, Health and Sport, 2017)
Activation of free radical oxidation is one of the key elements of the diabetes mellitus pathogenesis that leads to structural and functional disruption of membranes. Oxidative stress and imbalance between its intensity and the antioxidant system condition, comply with the data obtained from the literature, play an important role in the development of this disease complications. The defect of β-cells of Langerhans islets caused by hyperglycemia enhanced oxidative stress, is also substantially affect the progression of diabetes and its complications. The aim of this work is to study the status of lipid peroxidation and the antioxidant system at experimental diabetes, as well as to study the effectiveness of arginine corrective action. Wistar outbreeding white rats were used in the study, with the weight of 180-200 g. Comply with objectives of the work, animals were ranked into 3 groups: group 1– 20 animals that were not subjected to any influence; they served as control; group 2 – 30 animals in which diabetes mellitus was simulated; group 3 – 30 animals were aimed to receive a 7 % arginine solution, against the backdrop of diabetes. Diabetes was modeled with an intraperitoneal three times delivery of alloxan at a dose of 7.5 ml, with 5 days interval. Delivery of alloxan have been carried out with the animals free drinking of 5% fructose solution. The experiment lasted 30 days. Scientists witnessed 100% survival of experimental rats while applying this model. Activation of lipid peroxidation was detected with the alloxan diabetes model, as evidenced by an increase in the MDA and diene conjugates content in blood serum. There is a decrease in the catalase and superoxide dismutase activity at the experimental diabetes. Corrective action of arginine has led to a decrease in lipid peroxidation (LPO) processes and to the antioxidant system activation.